MRI Texture Analysis Reveals Deep Gray Nuclei Damage in Amyotrophic Lateral Sclerosis. - Albuquerque, Milena; Anjos, Lara G.V.; Maia Tavares de Andrade, Helen; Oliveira, Márcia S.; Castellano, Gabriela; Junqueira Ribeiro de Rezende, Thiago; Nucci, Anamarli; Cavalcante França Junior, Marcondes (Journal of Neuroimaging, 2016)
Background and Purpose: Amyotrophic Lateral Sclerosis (ALS) is characterized by extensive corticospinal damage, but extrapyramidal involvement is suggested in pathological studies. Texture analysis (TA) is an image processing technique that evaluates the distribution of gray levels between pixels in a given region of interest (ROI). It provides quantitative data and has been employed in several neurodegenerative disorders. Here, we used TA to investigate possible deep gray nuclei (DGN) abnormalities in a cohort of ALS patients. Methods: Thirty-two ALS patients and 32 healthy controls underwent MRI in a 3T scanner. The T1 volumetric sequence was used for DGN segmentation and extraction of 11 texture parameters using the MaZda software. Statistical analyses were performed using the Mann-Whitney non-parametric test, with a significance level set at α = 0.025 (FDR-corrected) for TA. Results: Patients had significantly higher values for the parameter correlation (CO) in both thalami and in the right caudate nucleus compared to healthy controls. Also, the parameter Inverse Difference Moment or Homogeneity (IDM) presented significantly smaller values in the ALS group in both thalami. Conclusions: TA of T1 weighted images revealed DGN alterations in patients with ALS, namely in the thalami and caudate nuclei.